2022
DOI: 10.3389/fnut.2022.832641
|View full text |Cite
|
Sign up to set email alerts
|

Water and Beverages Intake Among Workers Amid the COVID-19 Pandemic in Indonesia

Abstract: As the COVID-19 pandemic hit worldwide in the early 2020, people were urged to alter their behavior to prevent disease spread, thus, led to change water intake. This study aimed to analyze water and beverage intake among health workers and general workers during COVID-19 pandemic in Indonesia. This study was a comparative descriptive study where the participants were 20–45-year-old health workers and general workers in Indonesia. Data collected included demographic, water and beverage intake, physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Participants who reported TFI below 0.4 L/day or higher than 6 L/day were excluded from the analysis. 8,25 TFI for all participants' (n=87) was 2,216.0 ± 433.4 mL/day. The median of urine colour was 3 (1-7).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Participants who reported TFI below 0.4 L/day or higher than 6 L/day were excluded from the analysis. 8,25 TFI for all participants' (n=87) was 2,216.0 ± 433.4 mL/day. The median of urine colour was 3 (1-7).…”
Section: Methodsmentioning
confidence: 92%
“…TFI > 2,000 ml/day categorized as adequate. 25 Participants were examined for urine colour on Saturday by collecting urine taken at 2.00 p.m. -8.00 p.m. 26 This study evaluated urine colour using the eight-shade urine colour scale published by Armstrong. A transparent urine collection container was placed against a plain white background in a well-lit room.…”
Section: Methodsmentioning
confidence: 99%
“…Based on sex, more women achieved water recommendation compared to men (75% vs. 67%) (8). A study by Sunardi et al on fluid intake during the pandemic among workers showed that total water intake was 1,882 (1,473-2,433) ml/day, which was lower than the survey in 2016 (10).…”
Section: Introductionmentioning
confidence: 83%
“…Inadequate water intake is correlated with metabolism impairment, diabetes mellitus and body weight management. 61 , 62 Water intake during the pandemic varied across the literature, in Indonesia, the COVID-19 related lockdown has led to inadequate daily water intake [1882 (147–2433) mL/day] among workers. 62 Similarly, Al-Domi et al reported that 31.4% of adult people in Jordan did not achieve their adequate water intake (≤8 cups) during the COVID-19 pandemic lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…61 , 62 Water intake during the pandemic varied across the literature, in Indonesia, the COVID-19 related lockdown has led to inadequate daily water intake [1882 (147–2433) mL/day] among workers. 62 Similarly, Al-Domi et al reported that 31.4% of adult people in Jordan did not achieve their adequate water intake (≤8 cups) during the COVID-19 pandemic lockdown. 63 In comparison, Bailly et al in their study assessed the impact of the lockdown in France on weight loss and body composition modifications in subjects participating in a weight loss program and found that there has been a slight increase in the TBW percentage by 0.2 at pre, 0.6 during and 0.1 after lockdown.…”
Section: Discussionmentioning
confidence: 99%